A pyrophosphate-activated nanochannel inspired by a TRP ion channel. Issue 85 (9th October 2019) - Zhu, Fei; Yang, Guanxing; Dhinakaran, Manivannan Kalavathi; Wang, Rui; Song, Miaomiao; Li, Haibing
Abstract : An artificial pyrophosphate (PPi) selectively activated nanochannel has been successfully constructed via introducing calix[4]arene receptors into a biomimetic nanochannel. Abstract : A pyrophosphate (PPi) selectively activated potassium channel was constructed via introducing the isoniazid functionalized calix[4]arene (C4NP) into a biomimetic nanochannel. The activation mechanism is mainly due to the changing of the inner surface charge and wettability of the nanochannel caused by PPi binding.